Constituting affective identities: Understanding the communicative construction of identity in online men's rights spaces. (January 2023) - Eddington, Sean M; Jarvis, Caitlyn M; Buzzanell, Patrice M
The present study examined how identity is affectively organized online in an online men's rights community, responding to calls to explore how sites like Reddit serve as spaces that host and support varied misogynist language and communities. We utilized scholarship of affective organizing and communicative constitution of organizations to study the identity construction through the social and communicative processes that facilitate and limit online communication. We analyzed 35, 643 comments from a popular men's rights community to interrogate how affective and gendered organizing contributed to identity construction using text mining, semantic network analyses, and qualitative analyses. Our findings revealed that affect was not merely prominent in the forum but served as a constitutive means through which the members of the men's rights community constructed their identity individually and within their Reddit community. We advance an affect-centered approach within organizational communication scholarship, theorizing how masculinity is constituted through the interplay of affective contradictions, affective sensemaking, and affective identification.